Cutaneous epithelioid hemangioma of atypical location: a case report - Murilo O. L. Carapeba; Benício R. Junior; Mariana V. Cervelatti; Fernanda A. L. Guaresemin; Paula A. L. Guaresemin; Marilda A. M. M. Abreu (Sociedade Brasileira de Patologia Clínica, 2015)
The epithelioid hemangioma, also called angiolymphoid hyperplasia with eosinophilia, is a rare benign vascular tumor that manifests as nodules. Histopathological examination shows vascular spaces of various sizes lined by prominent endothelium, and inflammatory infiltrates composed of eosinophils, histiocytes, mast cells and lymphocytes. We report a case of epithelioid hemangioma characterized by skin lesion in the left upper limb. This is an unusual location, since the lesions occur most often in the head and neck.